Topical anesthetic versus lidocaine infiltration in arteriovenous fistula cannulation - Anisha George; Pratish George; Deepak Masih; Nina Philip; David Shelly; Jasmin Das; Timothy Rajamanickam (Wolters Kluwer Medknow Publications, 2014)
Background: End stage renal disease (ESRD) patients on maintenance hemodialysis undergo arterio-venous fistula (AVF) cannulation prior to each hemodialysis session for blood access. Prior to cannulation lidocaine infiltration is done, which is often perceived as painful. Eutectic mixture of local anesthetic (EMLA) has been found to significantly reduce pain associated with radial artery cannulation compared with lidocaine infiltration. Aims: To evaluate the efficacy of EMLA compared to infiltration of lidocaine in hemodialysis patients for AVF cannulation. Materials and Methods: A single-centre, crossover study of patients with an AVF on regular maintenance hemodialysis was performed in the dialysis unit of a tertiary care teaching hospital. The site of AVF, number of attempts for AVF cannulation and cannula insertion time were recorded. The patients were asked about the acceptability of application of the anesthetic, delay between anesthetic and cannulation and to score the pain on cannulation. Results: Fifty patients were included in the study. With the visual analog scale, pain score on infiltration was 4.8. Pain score on cannulation after topical application was 2.9 and after infiltration, 2.0. The number of attempts for cannulation and the cannula insertion time were similar. Anesthesia was more stressful in the injectable group rather than the topical group (P < 0.001). Delay between anesthetic and cannulation was unacceptable in the topical group (P < 0.001). Patient compliance was better during infiltration compared to topical (P < 0.005). Mean pain score during infiltration of anesthetic was significantly higher than cannulation pain after either anesthetic, although pain on cannulation was higher in the topical group (P < 0.001). Conclusions: EMLA offers a suitable alternative to lidocaine infiltration for patients using AVF for blood access.